2016
DOI: 10.2337/db15-1333
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD93 Is Involved in Metabolic Dysregulation but Does Not Influence Carotid Intima-Media Thickness

Abstract: Type 2 diabetes and cardiovascular disease are complex disorders involving metabolic and inflammatory mechanisms. Here we investigated whether sCD93, a group XIV c-type lectin of the endosialin family, plays a role in metabolic dysregulation or carotid intima-media thickness (IMT). Although no association was observed between sCD93 and IMT, sCD93 levels were significantly lower in subjects with type 2 diabetes (n = 901, mean ± SD 156.6 ± 40.0 ng/mL) compared with subjects without diabetes (n = 2,470, 164.1 ± 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Specific genetic loci that affect the microvascular endothelial cells in glomeruli might contribute to this phenomenon [22,[26][27][28][29][30]. Although the association between sCD93 and cardiovascular disease has been studied, the results are complex, depending on the study population and the target vessels [6,7,17,31]. In our diabetic patients, there was no difference in macrovascular complications, such as coronary artery disease, peripheral artery disease, and CVA, between the low and high serum sCD93 groups.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Specific genetic loci that affect the microvascular endothelial cells in glomeruli might contribute to this phenomenon [22,[26][27][28][29][30]. Although the association between sCD93 and cardiovascular disease has been studied, the results are complex, depending on the study population and the target vessels [6,7,17,31]. In our diabetic patients, there was no difference in macrovascular complications, such as coronary artery disease, peripheral artery disease, and CVA, between the low and high serum sCD93 groups.…”
Section: Discussionmentioning
confidence: 69%
“…First, the number of human study subjects was relatively small to perform additional subgroup analyses. Previously, several studies measured sCD93 in a larger number of human subjects compared with the current study [7,17,31]. However, no previous report investigated the clinical implication of sCD93 in a DN-centric view based on the eGFR and the ACR, which is the novel part of our study despite the relatively small number of participants.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…It was previously found that murine CD93 contributes to the removal of apoptotic cells in vivo [ 37 ]. Interestingly, Strawbridge et al demonstrated the function of soluble CD93 (sCD93) in glucometabolic regulation, and lower sCD93 levels might be related to type 2 diabetes patients who have a higher cardiovascular disease risk [ 38 ]. However, no research has focused on the mechanism of action of CD93 molecules in aneurysmal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is over-expressed during inflammation, and the soluble form (soluble CD93) is increased in various inflammatory conditions. Soluble CD93 is associated with premature myocardial infarction, coronary artery disease, and other inflammatory conditions [38][39][40] , with reduced levels of the soluble CD93 related to metabolic dysregulation 41 . Thus, the release of soluble CD93 has been implicated in response to stressors, such as inflammatory, immune, and angiogenic mediators.…”
Section: Protein-bound Uremic Toxins Endothelial Function and The Cmentioning
confidence: 99%